Bibliometric Analysis of the Development of Food Security Studies in the Perspective of Agricultural Economics - Judijanto, Loso (West Science Agro, 2025)
This study presents a comprehensive bibliometric analysis of global research on food security through the lens of agricultural economics, aiming to uncover the intellectual structure, thematic evolution, and collaborative networks within the field. Using data retrieved from the Scopus database (2000–2025) and analyzed through VOSviewer, the study identifies key trends, influential authors, countries, and emerging research fronts. Keyword co-occurrence mapping reveals that food security remains the central theme, closely linked with agricultural production, climate change, sustainable development, and innovation in agricultural practices. Temporal overlay analysis shows a thematic shift from poverty and nutrition toward climate-smart agriculture and digital transformation, while density visualization highlights research intensity around sustainability and production. Author and country co-authorship networks indicate strong regional clusters, with the United States, India, and the United Kingdom playing leading roles in shaping the discourse. The findings offer practical implications for policymakers and theoretical contributions by expanding the analytical dimensions of agricultural economics in addressing complex food system challenges. Limitations are acknowledged in database scope and keyword-level interpretation, providing directions for further qualitative and regional-specific exploration.